Decoding Salivary ncRNAomes as Novel Biomarkers for Oral Cancer Detection and Prognosis - Subhadeep Das; Sampad Basak; Soumyadev Sarkar (Non-Coding RNA)
Oral cancer (OC) ranks among the most prevalent head and neck cancers, becoming the eleventh most common cancer worldwide with ~350,000 new cases and 177,000 fatalities annually. The rising trend in the occurrence of OC among young individuals and women who do not have tobacco habits is escalating rapidly. Surgical procedures, radiation therapy, and chemotherapy are among the most prevalent treatment options for oral cancer. To achieve better therapy and an early detection of the cancer, it is essential to understand the disease’s etiology at the molecular level. Saliva, the most prevalent body fluid obtained non-invasively, holds a collection of distinct non-coding RNA pools (ncRNAomes) that can be assessed as biomarkers for identifying oral cancer. Non-coding signatures, which are transcripts lacking a protein-coding function, have been identified as significant in the progression of various cancers, including oral cancer. This review aims to examine the role of various salivary ncRNAs (microRNA, circular RNA, and lncRNA) associated with disease progression and to explore their functions as potential biomarkers for early disease identification to ensure better survival outcomes for oral cancer patients.